2022
DOI: 10.1177/17479541221088640
|View full text |Cite
|
Sign up to set email alerts
|

Description of collective behaviour in football according to the level of competence in representative tasks from positional data: Systematic review

Abstract: The aim of this systematic review is to provide a base of knowledge from studies that have dealt with the description of collective behaviour in young footballers according to the level of competence associated to that age group, taking representative tasks from positional data as our starting point. Following the PRISMA statement a systematic revision was carried out on three meta-search engines (PubMed, Web of Science and SportDiscus). The following key words were used in the search: football, tactical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The distance between dyads (pairs of players) also increases with age. This indicates that older players tend to maintain a greater spatial separation from their teammates (Nieto et al, 2022). This result may show that average team age may be effective on teams' collective behaviour.…”
Section: Out Of Possessionmentioning
confidence: 87%
“…The distance between dyads (pairs of players) also increases with age. This indicates that older players tend to maintain a greater spatial separation from their teammates (Nieto et al, 2022). This result may show that average team age may be effective on teams' collective behaviour.…”
Section: Out Of Possessionmentioning
confidence: 87%
“…A recent systematic review (19) has tried to collect existing knowledge on the evolution of CB in representative tasks of different groups of young soccer players (24). From the review, it can be concluded that there are three fundamental requirements to consider in the works that attempt to address the study of soccer competition from a longitudinal point of view: (a) the tasks where the CB of the players is analyzed must be representative (35); (b) if it is not possible to undertake a “pure” longitudinal study, at least players of various age categories are evaluated in the same period, corresponding to the same training framework (e.g., high competition and homogeneous); and (c) contextualize the game action based on the phases and areas of the pitch (because of its strategic particularities), offering a greater degree of relevance in the description of the behavioral display.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, there are still few studies that, from an ecological perspective (31), respect the competition formats in which they participate, and without intervening in them, they have evaluated the CB of the players in the training process. For this reason, continuing to investigate what soccer competition is like and how it evolves over time from the rookie and inexperienced player to the most advanced levels of expertise could allow us to focus on the requirements of each stage, with the aim of optimizing an intervention model that favors their preparation and progression (19). The main applicability of knowing the CB path allows for the possibility of offering young players a personalized design of training environments that assist skill learning (15).…”
Section: Introductionmentioning
confidence: 99%